Evidence for Widespread Associations between Neotropical Hymenopteran Insects and Actinobacteria - Matarrita-Carranza, Bernal; Moreira-Soto, Rolando D.; Murillo-Cruz, Catalina; Mora, Marielos; Currie, Cameron R.; Pinto-Tomas, Adrián A. (Frontiers in Microbiology, 2017)
The evolutionary success of hymenopteran insects has been associated with complex physiological and behavioral defense mechanisms against pathogens and parasites. Among these strategies are symbiotic associations between Hymenoptera and antibiotic-producing Actinobacteria, which provide protection to insect hosts. Herein, we examine associations between culturable Actinobacteria and 29 species of tropical hymenopteran insects that span five families, including Apidae (bees), Vespidae (wasps), and Formicidae (ants). In total, 197 Actinobacteria isolates were obtained from 22 of the 29 different insect species sampled. Through 16S rRNA gene sequences of 161 isolates, we show that 91% of the symbionts correspond to members of the genus Streptomyces with less common isolates belonging to Pseudonocardia and Amycolaptosis. Electron microscopy revealed the presence of filamentous bacteria with Streptomyces morphology in brood chambers of two different species of the eusocial wasps. Four fungal strains in the family Ophiocordycipitacea (Hypocreales) known to be specialized insect parasites were also isolated. Bioassay challenges between the Actinobacteria and their possible targeted pathogenic antagonist (both obtained from the same insect at the genus or species level) provide evidence that different Actinobacteria isolates produced antifungal activity, supporting the hypothesis of a defensive association between the insects and these microbe species. Finally, phylogenetic analysis of 16S rRNA and gyrB demonstrate the presence of five Streptomyces lineages associated with a broad range of insect species. Particularly our Clade I is of much interest as it is composed of one 16S rRNA phylotype repeatedly isolated from different insect groups in our sample. This phylotype corresponds to a previously described lineage of host-associated Streptomyces. These results suggest Streptomyces Clade I is a Hymenoptera host-associated lineage spanning several new insect taxa and ranging from the American temperate to the Neotropical region. Our work thus provides important insights into the widespread distribution of Actinobacteria and hymenopteran insects associations, while also pointing at novel resources that could be targeted for the discovery of active natural products with great potential in medical and biotechnological applications.